Blameless Guilt: The Case of Carer Guilt and Chronic and Terminal Illness. Issue 1 (1st January 2018) - Bennett, Matthew
Abstract: My ambition in this paper is to provide an account of an unacknowledged example of blameless guilt that, I argue, merits further examination. The example is what I call carer guilt: guilt felt by nurses and family members caring for patients with palliative-care needs. Nurses and carers involved in palliative care often feel guilty about what they perceive as their failure to provide sufficient care for a patient. However, in some cases the guilty carer does not think that he has the capacity to provide sufficient care; he has, in his view, done all he can. These carers cannot legitimately be blamed for failing to meet their own expectations. Yet despite acknowledging their blamelessness, they nonetheless feel guilty. My aims are threefold: first, to explicate the puzzling nature of the carer guilt phenomenon; second, to motivate the need to solve that puzzle; third, to give my own account of blameless guilt that can explain why carers feel guilty despite their blamelessness. In doing so I argue that the guilt experienced by carers is a legitimate case of guilt, and that with the right caveats it can be considered an appropriate response to the progressive deterioration of someone for whom we care.